Assessing vulnerability to HIV of migrant female students: A Mixed method exploratory study - Vaishali Gautam; Arun Kumar Sharma; Sanjay Bhasin (Social Medicine Publication Group, 2021)
Background and methodology Female migrants have been identified to be at higher risk of HIV infection in comparison with male migrants, but the evidence is limited. The present study was conducted among novel group i.e. migrant female college student using a mixed-method approach to explore their vulnerability and risk to acquire HIV infection. Sample of 100 female migrant college students of Delhi University, of the age 18 and 23 years were selected from March 2015 to April 2016 and administered semi-closed questionnaire followed by in-depth interviews. Results Mean age of sexual initiation was 18.7 years. Twenty-one percent respondents had inadequate HIV related knowledge and 10% of respondents showed high-risk sexual behaviour as none used a condom consistently. Statistically, a significant association was observed between respondent's high-risk behaviour and having friends who were sexually exposed (p < 0.005), also with respondent's partner's current place of residence (p